Normirovanie specializirovannosti i koordinacionnoj sloznosti trenirovocnych nagruzok junych futbolistov - Zolotarev, A. P. (Teorija i Praktika fiziceskoj Kul'tury, 2004)
The purpose of the research was the development of technology of normalization of the specialty and a coordination complexity of training loadings and an experimental substantiation of their age dynamics at the stages of long-term training of football players.